Inaugural Editorial - Safaei, Babak (Archives of Advanced Engineering Science, 2023)
Writing an editorial note for the first volume of the new journal of Archives of Advanced Engineering Science (AAES) is a great glory and honor for me. The scope of AAES is not limited to a single aspect of engineering and science and covers various subfields in the applied and fundamental engineering sciences. Particularly, articles with interdisciplinary nature are welcomed. A warm welcome to the inaugural issue of AAES, which is a new exciting title and subject for Bon View Press portfolio journals for 2023. AAES is a new beginning for engineering development in the way to advanced engineering science. I am fortunate and honored to be a member of AAES and take the responsibility of Editor-in-Chief. As can be witnessed in journal title, this pioneering journal aims to address and understand Engineering Science. Subject fields include, but are not limited to, Mechanical Engineering, Electrical and Informatics Engineering, Civil Engineering, Chemical Engineering, Material Engineering, Computer Engineering, Environmental Engineering, Renewable Energy and Resources, Technology and Applications, Sustainable Development and Interdisciplinary science. Today, we feel great happiness to publish the first issue of our journal in November 2023. This issue has six articles on different interesting topics in engineering science. I believe that AAES is providing a vigorously open-access, peer-reviewed, leading platform aiming at publishing the most valuable and Influential research works in the main basic areas of engineering science around the world. To enhance the standard of the journal through publishing high quality papers, we followed the main practices of Committee on Publication Ethics (COPE) and accordingly handled research and publication misconduct. Strict ethical guidelines for editors, authors, and peer reviewers were clearly presented. We introduced desk reject, double-blind peer-review by at least two anonymous reviewers and plagiarism detection to guarantee high standards of AAES.